Fisioterapia manual en la gestación. - Díaz Valiente, Arely Liset (2024)
The present research work is a bibliographic documentary because its purpose lies in delving into physiotherapeutic knowledge and analyzing manual physiotherapy techniques in pregnancy through the collection of information that allows relating criteria and conceptualizations. The gestation process is accompanied by several physical and psychological changes in the mother, including adaptations at a biomechanical and musculoskeletal level, showing combined muscle weakness in the abdominal area, thus increasing lumbar lordosis and the angle of pelvic anteversion. Furthermore, due to hormonal factors, they favor hypermobility of ligaments and cartilage, generating instability in the lumbopelvic area; these changes are responsible for altering the maternal posture and, in many cases, causing painful dysfunctions, limiting daily activities, or even terminating the pregnancy to prevent the condition of mother and baby health. Manual physiotherapy can be used throughout pregnancy to maintain or restore body biomechanics. It balances the osteo-muscle-ligamentous structures, mitigating high-risk disorders in pregnant patients and allowing a faster recovery after childbirth. For this reason, in the research, the manual physiotherapy techniques used in pregnancy were known for this. A qualitative methodology with a documentary approach was applied through the search and analysis of information in recognized bibliographic sources; the benefits and importance of the application of manual physiotherapy during pregnancy observed that with just five or six sessions, the pain decreased significantly in 60% of pregnant women.